Makna Injil Berdasarkan Roma 1: 16-17 Dan Implementasinya Bagi Gereja Masa Kini - Kejar Hidup Laia (Sekolah Tinggi Teologi Arastamar Bengkulu, 2020)
The fall of the first man (Adam) into sin caused the man to lose the glory of God, man died and was separated from God. The gospel is glad tidings of Jesus Christ who died, rose again to save everyone who believes. To believe the gospel means to believe in the redemptive work of Christ, to reject the gospel is to reject salvation. In the Gospel God's truth is revealed to everyone who believes in Him. This truth is related to the absolute truth of God that no one has. The truth of God revealed in the Gospels is related to the truth that God has done through the death and resurrection of the Lord Jesus to save sinners. Salvation can only be received through faith. Faith is a gift from God given to humans so that they believe in Jesus Christ as Lord and Savior. The gospel gives hope and sets people free from death. To get salvation everyone must listen to the gospel. The task of evangelism is the responsibility of the Church (believers) to preach the message of salvation in the power of the Holy Spirit to sinners so that they repent and have faith in Jesus and become disciples who obey the Great Commission of the Lord Jesus.